2016
DOI: 10.1128/aac.00330-16
|View full text |Cite
|
Sign up to set email alerts
|

New Regimen for Continuous Infusion of Vancomycin in Critically Ill Patients

Abstract: Vancomycin remains a primary treatment for infections caused by Gram-positive bacteria resistant to ␤-lactam antibiotics, including methicillin-resistant Staphylococcus aureus (MRSA), methicillin-resistant Staphylococcus epidermidis (MRSE), and ampicillin-resistant enterococci (1). Despite extensive clinical use of vancomycin over recent years, the optimal dosing strategy for rapid achievement of therapeutic concentrations still remains a challenge for physicians. This is of particular interest for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 36 publications
4
68
0
1
Order By: Relevance
“…These findings are also consistent with data for other drugs that are renally cleared, such as gentamicin, where increased doses are required in the intensive care setting secondary to an illness‐induced hyperdynamic state and consequent increased volume of distribution . Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing . Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are also consistent with data for other drugs that are renally cleared, such as gentamicin, where increased doses are required in the intensive care setting secondary to an illness‐induced hyperdynamic state and consequent increased volume of distribution . Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing . Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary.…”
Section: Discussionsupporting
confidence: 87%
“…36 Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing. [37][38][39][40] Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary. Doses at the higher end of daily recommendations were required in older children, with 75% of children attaining therapeutic concentrations with doses >50 mg/kg/day.…”
Section: Discussionmentioning
confidence: 79%
“…However, initiation of a vancomycin CI calls for a loading dose that quickly reaches blood levels of 20-30 mg/L [11,15] to cover isolates with vancomycin MICs of 1-2 mg/L. Thus, loading doses of 15-20 mg/kg are often recommended [11,12] but may frequently lead to subtherapeutic concentrations [15][16][17][18] . A simulation study using a one-compartment model applied to critically ill patients showed that a loading dose of 35 mg/kg could be necessary [15] , but also resulted in a large proportion of patients with supratherapeutic vancomycin concentrations [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is administered to critically ill patients with multiple underlying diseases, such as heart failure, chronic renal disease, and cirrhosis of the liver. It is also administered postoperatively for wound infection treatment 7, 8. Thus, multiple pathology and resultant changes to normal physiology may be the reason for the unexplained PK variability among patients.…”
mentioning
confidence: 99%
“…It is also administered postoperatively for wound infection treatment. 7,8 Thus, multiple pathology and resultant changes to normal physiology may be the reason for the unexplained PK variability among patients.…”
mentioning
confidence: 99%